2020
DOI: 10.1186/s13027-020-00312-9
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of programmed cell death ligand 1 in patients with CIN and its correlation with human papillomavirus infection and CIN persistence

Abstract: Backround HPV causes specific cell-mediated immunity in the cervix. Mononuclear cells such as helper T cells (CD4+), cytotoxic T cells (CD8+), and dendritic cells play a critical role in the initiation of the HPV-specific immune response and destruction of virus-infected cervical epithelial cells. The programmed cell death ligand 1 (PD-L1) gene encodes an immune inhibitory receptor ligand and overexpression of PD-L1 inhibits T-cell activation and cytokine production. The aim of this study was to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…This is true not only for already established tumours, but also in precursor lesions. The study conducted by Usta et al showed how the expression of PDL-1 is higher when the degree of dysplasia of cervical epithelial cells is increased, and this expression is related to the presence of HPV infection [33].…”
Section: Human Papillomavirus Infectionmentioning
confidence: 99%
“…This is true not only for already established tumours, but also in precursor lesions. The study conducted by Usta et al showed how the expression of PDL-1 is higher when the degree of dysplasia of cervical epithelial cells is increased, and this expression is related to the presence of HPV infection [33].…”
Section: Human Papillomavirus Infectionmentioning
confidence: 99%
“…Standardized tissue preparation protocols were followed during the histopathological examination of cervical tissues as previously described [27]. Subsequently, anti-furin (1:100; Santa Cruz Biotechnology Inc., Dallas, TX, USA), anti-ki-67 (1:100; Santa Cruz Biotechnology Inc., Dallas, TX, USA), and anti-p16 (1:50; Santa Cruz Biotechnology Inc., Dallas, TX, USA) antibodies were applied.…”
Section: Immunohistochemistry and Evaluationmentioning
confidence: 99%
“…Indeed, the expression of PD-L1 is stronger at the level of the basal layer and of the intraepithelial capillaries due to the presence of T lymphocyte found respectively in the chorion and in the vascular lumen, thus carrying out the phenomenon of empirepolesis [69]. Epithelial cells resistant to this anti-tumor immune mechanism develop PD-L1 on their membrane which binds to lymphocyte PD1 thus generating an immune tolerance system responsible for the progression from intraepithelial neoplasia to cervical cancer [95].…”
Section: Pd-l1 and Tissue Alterations Predicting Papillomavirus Infectionmentioning
confidence: 99%
“…PD-L1 expression was observed in 81.25% of grade 3 cervical intraepithelial neoplasms in this study. Intraepithelial neoplasms and its correlation with the persistence of human papillomavirus infection, expression of PD-L1 in cervical epithelial and mononuclear cells gradually increases from the CIN 1 group without Papillomavirus positivity to at oncogenic risk towards the oncogenic group CIN II-III positive for highrisk oncogenic papillomavirus with a significant difference between the respective groups (p=0.0003 and p=0.0394) [95]. By evaluating the capacity for recurrence of neoplastic intraepithelial lesions of the cervix after conization by looking for the expression of TPX2 and PD-L1 in cells of the surgical margin, the authors noted that the positive PD-L1 level was significantly higher.…”
Section: Pd-l1 and Grades Of Intraepithelial Neoplasms Of The Cervixmentioning
confidence: 99%